Rehabilitation of COVID-19 convalescents and its impact on cardiovascular endpoints: propensity score matching analysis - G. Kh. Lasynova; I. A. Lakman; D. F. Gareeva; A. A. Agapitov; L. F. Sadikova; А. R. Sakhautdinov; V. N. Pavlov; N. Sh. Zagidullin (Российский кардиологический журнал)
Due to the large number of complications and decreased quality of life after coronavirus disease (COVID-19), physical and psychological rehabilitation of patients is relevant. However, the effectiveness of rehabilitation on endpoints has not yet been demonstrated.Aim. To determine the effectiveness of different rehabilitation options in hospitalized patients with COVID-19 on the development of long-term adverse cardiovascular events 1 year after discharge.Material and methods. In a single-center, non-randomized observational study, 3 groups of patients were formed after hospitalization with COVID-19: I — with telemedicine rehabilitation (n=118), II — with rehabilitation in a specialized department (n=46) and III — without rehabilitation (n=175). After 1-year followup, groups were compared regarding following endpoints: cardiovascular mortality, myocardial infarction, stroke, pulmonary embolism, atrial fibrillation and cardiovascular hospitalization. Propensity score matching analysis was used to optimize differences between comparison groups.Results. Rehabilitation after hospitalization of patients with COVID-19, both in the hospital and remotely for 1 year, helps to reduce cardiovascular hospitalization rate. In addition, remote rehabilitation reduces cardiovascular mortality.Conclusion. Both rehabilitation options reduce the incidence of cardiovascular hospitalization compared to no rehabilitation.